Volunteer Connect: A Volunteer Coordination Platform with Chatbot Assistance via Retrieval-Augmented Generation (International Journal of Scientific Research in Science and Technology, 2025)
Volunteer Connect is a web-based platform developed to enhance volunteer coordination and event management for non-profit organizations. The system offers tailored interfaces for both organizations and volunteers, ensuring a user-centric experience. Organizations can create events, utilize AI-powered auto-description for event postings, and notify volunteers via automated email alerts. Volunteers can register for events, track their participation, and interact with organizations and fellow volunteers through integrated real-time chat. Additionally, the platform features an AI-assisted chatbot that provides instant support and information, such as upcoming event details and participation tracking. Role-based access control ensures security and contextual experiences for different users. By addressing key challenges like inefficient communication, poor event visibility, and lack of engagement tools, Volunteer Connect improves the efficiency of community service coordination. This paper discusses the system’s architecture, key functionalities, challenges faced during development, and its potential impact on volunteerism.
Keywords: Volunteer Coordination; Web-Based Platform; AI-Powered Chatbot; Event Management; Non-Profit Organizations; Volunteer Engagement; Real-Time Tracking; Role-Based Access; Automated Certificate Generation; Social Impact Technology